Pengembangan UMKM Melalui Sosialisasi Pemasaran Berbasis E-Commerce - Titin Patimah; Fauzi Rahmatulloh; Hayya Bakhita Fauzi; Zahra Ardianti; Sindi Pradita Sari; Naila Azka Karimah; Aris Gunawan (Universitas Perjuangan Tasikmalaya, 2026)
MSMEs often face limitations in reaching a wider market. Generally, micro and small business actors have not been adaptive in using digital technology as an effort to increase profits for the businesses they manage. This socialization program is designed to provide understanding and practical skills regarding digital marketing that can help MSMEs expand their markets, encourage innovation in marketing strategies. In addition, this program is expected to increase the competitiveness of village MSMEs and encourage the community's economy in a sustainable manner. The results of the community service activities from this socialization activity are that MSME actors gain increased knowledge and motivation for business actors in utilizing digital media for promotion. However, in this activity, there are obstacles encountered, namely in the process of mentoring MSMEs, it was found that some business actors experienced difficulty in understanding the material, especially related to the use of digital technology. One of the main factors influencing this is the age of the MSME actors. Older MSME actors tend to have limitations in keeping up with technological developments.